THE STRUCTURE OF ORBITAL INJURIES AND ASSESSMENT OF THE SEVERITY OF INJURIES - Nilufar Kh. Ganieva; Ibragim I. Bakhriev (Central Asian Journal of Medicine, 2023)
The article reflects a comprehensive analysis of aspects of forensic-medical expertise of orbital trauma. The issues related to the peculiarities of forensic-medical assessment of isolated and combined orbital trauma at the present stage are presented. The difficulties of expertise in these conditions are considered, which are determined, on the one hand, by the interdisciplinary nature of this pathology, and on the other hand, by the imperfection of the legal framework. The necessity of reviewing and reforming the existing legislative basis of forensic-medical expertise is substantiated.